(untitled) (Bangladesh Journal of Plant Taxonomy, 2018)
The nuclear ribosomal DNA (nrDNA) internal transcribed spacers (ITS) sequences is extensively used in the plant molecular phylogenetics for plant taxonomic identification and DNA barcoding purposes because the nrDNA ITS gene is easy to amplify by using the universal primers, its length is shorter and thus easy to sequence, and has strong discrimination power to distinguish the taxon at the species level. The present molecular phylogenetic analysis of ITS nrDNA sequences focuses to determine the taxonomic status of an unresolved endemic taxon Kickxia abhaica D.A. Sutton (Family Plantaginaceae, tribe Antirrhineae) reported from Saudi Arabia. The analysis supports the transfer of K. abhaica under the genus Nanorrhinum.